Symptomatic Carotid Atherosclerotic Plaques Are Associated With Increased Infiltration of Natural Killer (NK) Cells and Higher Serum Levels of NK Activating Receptor Ligands - Bonaccorsi, Irene; Spinelli, Domenico; Cantoni, Claudia; Barillà, Chiara; Pipitò, Narayana; De Pasquale, Claudia; Oliveri, Daniela; Cavaliere, Riccardo; Carrega, Paolo; Benedetto, Filippo; Ferlazzo, Guido (Frontiers in Immunology, 2019)
A wide array of immune cells, including lymphocytes, is known to be present and to play a pathogenetic role in atherosclerotic lesions. However, limited information is currently available regarding the presence of Natural Killer (NK) cell subsets within vessel plaque and, more in general, regarding their role in human atherosclerosis. We evaluated the distribution of NK cells in human carotid atherosclerotic plaques, dissecting asymptomatic and symptomatic patients (identified as affected by stroke, transient ischemic attack or amaurosis fugax within 6 months) with the aim of shedding light on the putative contribution of NK cells to the pathogenic process that leads to plaque instability and subsequent clinical complications. We observed that carotid plaques were consistently infiltrated by NK cells and, among them, CD56brightperforinlow NK cells were abundantly present and displayed different markers of tissue residency (i.e. CD103, CD69 and CD49a). Interestingly, carotid atherosclerotic plaques of symptomatic patients showed a higher content of NK cells and an increased ratio between CD56brightperforinlow NK cells and their CD56dimperforinhigh counterpart. NK cells isolated from plaques of symptomatic patients were also stronger producers of IFN-γ. Analysis of the expression of NK activating receptor ligands (including MICA/B, ULBP-3 and B7-H6) in atherosclerotic carotid plaques revealed that they were abundantly expressed by a HLA-DR+CD11c+myeloid cell population resident in the plaques. Remarkably, sera of symptomatic patients contained significant higher levels of soluble ligands for NK activating receptors. Our observations indicate that CD56bright NK cells accumulate within human atherosclerotic lesions and suggest a possible contribution of NK cells to the process determining plaque instability.